Regenerated cellulose–lignin composite films for efficient removal of cationic dyes and Pb(II) ions from aqueous media - Heba kandil; Iván Rivilla; Jalel Labidi; Ahmed E. Abdelhamid (Journal of Environmental Chemical Engineering, 2026)

Boosting sunscreen efficiency with DES‑extracted lignins from olive tree pruning residues - Irene Gómez-Cruz; Irene Olaizola; Jesús M. Bañales; André M. Da Costa; Armando J.D. Silvestre; Eulogio Castro; Jalel Labidi (Food and Bioproducts Processing, 2026)

Antheraea pernyi silk fibroin fiber-reinforced biodegradable mulch film for controlled herbicide delivery and sustainable weed suppression - Tong Zhang; Haneef Tariq; Jalel Labidi; Chandika Gunathilake; Yong-Ming Chen; Murat Kaya; Lian-Sheng Zang (Chemical Engineering Journal, 2026)

Environmental assessment of olive tree pruning valorization via deep eutectic Solvents: Toward a circular and sustainable biorefinery model - Irene Gómez-Cruz; Amaia Morales; Eulogio Castro; Jalel Labidi (Waste Management, 2026)

Iridium catalysts screening for mild organosolv lignin depolymerization - Najiba Mel; Izaskun Dávila; Xabier Erdocia; Jalel Labidi (Journal of Environmental Chemical Engineering, 2026)

Microwave-assisted valorization of glycerol for efficient production of 1,3-dioxolanes and 1,3-dioxanes catalyzed by acid-activated clay - Rassil Hayder; Jalel Labidi; Néji Besbes; Madiha Kamoun Mhiri (Euro-Mediterranean Journal for Environmental Integration, 2025)

Cellulose nanofibers as effective mediator for optical chemical sensors for heavy metal ions detection - Mahsa Mousavi Langari; Federica Mandoj; Giuseppe Pomarico; M. Mirari Antxustegi; Roberto Paolesse; Jalel Labidi; Larisa Lvova (Carbohydrate Polymers, 2025)

Enhancing lignocellulosic biomass pretreatment with choline chloride-based deep eutectic solvents - Farida Baraka; Mahsa Mousavi Langari; Itsasne Beitia; Izaskun Dávila; Jalel Labidi; Amaia Morales; Leyre Sillero (Journal of Environmental Chemical Engineering, 2025)

Green procedure for grafting polypeptide onto cellulose nanofibers - Farida Baraka; José Ignacio Santos; Mahsa Mousavi Langari; Iván Rivilla; Jalel Labidi (Chemical Engineering Journal, 2025)

The emergence of nanocellulose aerogels in CO2 adsorption - Farida Baraka; Jalel Labidi (Science of The Total Environment, 2024)

Nanocellulose-based sensors in medical/clinical applications: The state-of-the-art review - Mahsa Mousavi Langari; Maryam Nikzad; Jalel Labidi (Carbohydrate Polymers, 2023)

Valorization of Marine Waste: Use of Industrial By-Products and Beach Wrack Towards the Production of High Added-Value Products - Vita Rudovica; Ana Rotter; Susana P. Gaudêncio; Lucie Novoveská; Füsun Akgül; Linn Kristin Akslen-Hoel; Diogo A. M. Alexandrino; Olga Anne; Lauris Arbidans; Miroslava Atanassova; Magdalena Bełdowska; Jacek Bełdowski; et al. (Frontiers in Marine Science, 2021)
Biomass is defined as organic matter from living organisms represented in all kingdoms. It is recognized to be an excellent source of proteins, polysaccharides and lipids and, as such, embodies a tailored feedstock for new products and processes to apply in green industries. The industrial processes focused on the valorization of terrestrial biomass are well established, but marine sources still represent an untapped resource. Oceans and seas occupy over 70% of the Earth’s surface and are used intensively in worldwide economies through the fishery industry, as logistical routes, for mining ores and exploitation of fossil fuels, among others. All these activities produce waste. The other source of unused biomass derives from the beach wrack or washed-ashore organic material, especially in highly eutrophicated marine ecosystems. The development of high-added-value products from these side streams has been given priority in recent years due to the detection of a broad range of biopolymers, multiple nutrients and functional compounds that could find applications for human consumption or use in livestock/pet food, pharmaceutical and other industries. This review comprises a broad thematic approach in marine waste valorization, addressing the main achievements in marine biotechnology for advancing the circular economy, ranging from bioremediation applications for pollution treatment to energy and valorization for biomedical applications. It also includes a broad overview of the valorization of side streams in three selected case study areas: Norway, Scotland, and the Baltic Sea.

Barrier properties of cellulose nanofiber film as an external layer of particleboard - Aneta Gumowska; Grzegorz Kowaluk; Jalel Labidi; Eduardo Robles (Clean Technologies and Environmental Policy, 2019)

Assessment of biorefinery process intensification by ultrasound technology - Araceli García; María González Alriols; Walter Wukovits; Anton Friedl; Jalel Labidi (Clean Technologies and Environmental Policy, 2014)